Multidose Streptozotocin Induction of Diabetes in BALB/c Mice Induces a Dominant Oxidative Macrophage and a Conversion of TH1 to TH2 Phenotypes During Disease Progression - Naxin Sun; Guiwen Yang; Heng Zhao; Huub F. J. Savelkoul; Liguo An (Mediators of Inflammation)
Macrophages (Mp) are implicated in both early and late phases in type 1 diabetes development. Recent study has suggested that a balance between reductive Mp (RMp) and oxidative Mp (OMp) is possible to regulate TH1/TH2 balance. The aim of this study is to investigate the redox status of peritoneal Mp and its cytokine profile during the development of autoimmune diabetes induced by multiple low-dose streptozotocin in BALB/c mice. Meanwhile, the polarization of TH1/TH2 of splenocytes or thymocytes was also examined. We found that peritoneal Mp appeared as an “incomplete” OMp phenotype with decreased icGSH along with disease progression. The OMp showed reduced TNF-α, IL-12, and NO production as well as defective phagocytosis activity compared to nondiabetic controls; however, there was no significant difference with IL-6 production. On the other hand, the levels of IFN-γ or IL-4 of splenocytes in diabetic mice were significantly higher compared to the control mice. The ratio of IFN-γ to IL-4 was also higher at the early stage of diabetes and then declined several weeks later after the occurrence of diabetes, suggesting a pathogenetic TH1 phenotype from the beginning gradually to a tendency of TH2 during the development of diabetes. Our results implied that likely OMp may be relevant in the development of type 1 diabetes; however, it is not likely the only factor regulating the TH1H/TH2 balance in MLD-STZ-induced diabetic mice.